The Applied Effectiveness of Clay Art Therapy for Patients With Parkinson's Disease - Young-Sil Bae PhD, RN; Dong-Hee Kim PhD, RN (SAGE Publishing, 2018)
This study investigates how clay art therapy affects Parkinson's disease patients' overall mental and physical condition as well as future treatment potentiality. The research was nonequivalent control groups pre and post study. A total of 54 patients with Parkinson's disease (control = 28, experimental = 26) were recruited from 3 setting locations in South Korea. Test measures were completed before and after the 16 sessions. The experimental group received two 80-minute evaluations per week for 8 weeks. Demographic information: hand dexterity, self-expression, mood depression, and quality of life measurements. There were significant differences in hand dexterity ( t = 4.96, P < .001), self-expression ( t = 3.74, P < .001), mood depression ( t = −11.85, P < .001), and quality of life ( t = 8.07, P < .001) between the 2 groups. Further research and development of clay art therapy can advocate the benefits, highlight practicality and demonstrate the possibility for its usage as a treatment methodology.